Integrating community-based adopt-a-tree programs with sustainable agrotourism: A Pathway to inclusive green growth in Merangin Regency - Zulgani, Zulgani; Junaidi, Junaidi; Hastuti, Dwi; Asfahani, Fadwa Rhogib; Lubis, Wahdan Adillah Amri (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
The integration of conservation initiatives with tourism development has emerged as an important strategy for promoting sustainable rural development. This study examines how community-based Adopt-a-Tree (AAT) programs are integrated into sustainable agrotourism in Merangin Regency, Indonesia, and how this integration contributes to environmental conservation and local livelihood opportunities. A qualitative case study approach was employed, drawing on data from in-depth interviews, focus group discussions, field observations, and supporting documents related to the implementation of tree adoption programs in Rantau Kermas and Guguk villages. Thematic analysis was conducted using NVivo 15 to identify patterns and relationships across stakeholder perspectives. The findings indicate that AAT programs function as a community-driven conservation mechanism that supports forest restoration, biodiversity protection, and increased environmental awareness among residents and visitors. The analysis also reveals that stakeholder collaboration, training activities, and local governance support are important for sustaining the implementation of conservation initiatives. In addition, integrating tree adoption with agrotourism creates new livelihood opportunities through eco-tourism services, agroforestry products, and community-based tourism activities. However, several challenges remain, including limited technical capacity, unequal participation opportunities, and constraints in institutional and financial support. Overall, the study demonstrates that AAT programs can serve as an effective model for integrating conservation initiatives with sustainable agrotourism development while supporting inclusive rural livelihoods and long-term environmental stewardship